Physical activity in prevention and treatment of type 2 diabetes mellitus - Klimek, Monika; Knap, Joanna; Masternak, Marta; Reda, Mateusz (Journal of Education, Health and Sport, 2019)
Type 2 diabetes in more than 70% of cases is caused by overweight and obesity. In many cases, a proper diet and increased physical activity are effective in the prevention and treatment of insulin resistance and pre-diabetes, which usually prevents the development of the disease. However, the recommendations for physical activity in type 2 diabetics differ from those for healthy people. The paper presents an analysis of recommendations concerning physical activity in the prevention and treatment of type 2 diabetes.